2002
DOI: 10.1300/j008v19n01_05
|View full text |Cite
|
Sign up to set email alerts
|

A Classroom-Based Intervention to Reduce Disruptive Behaviors

Abstract: The present study investigated the effectiveness of an intervention comprising posted classroom rules, token economy, response cost, and mystery motivators in reducing disruptive classroom behavior. Participants were three male second grade students identified as having oppositional defiant disorder. To serve as an additional control, a class composite was formed using five male classmates whose behavior was judged appropriate. The study employed a multiple baseline across subjects design. Results showed an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was hypothesized the proposed study would replicate the results of prior studies, which documented the effectiveness of the Mystery Motivator intervention in eliciting behavioral change in both individual students and classrooms (Bennett, 2010;DeMartini-Scully, Bray, & Kehle, 2000;Hoag, 2006;Kehle et al, 1998;Kraemer et al, 2012;LeBlanc, 1998;Madaus et al, 2003;Matovic, 2010;Moore et al, 1994;Mottram et al, 2002;Murphy et al, 2007;Musser et al, 2001;Robinson & Sheridan, 2000;Schanding & Sterling-Tumer, 2010). Thus, it was hypothesized that the Mystery Motivator intervention would lead to a decrease in dismptive classroom behavior.…”
Section: Purpose Of the Studymentioning
confidence: 70%
See 1 more Smart Citation
“…It was hypothesized the proposed study would replicate the results of prior studies, which documented the effectiveness of the Mystery Motivator intervention in eliciting behavioral change in both individual students and classrooms (Bennett, 2010;DeMartini-Scully, Bray, & Kehle, 2000;Hoag, 2006;Kehle et al, 1998;Kraemer et al, 2012;LeBlanc, 1998;Madaus et al, 2003;Matovic, 2010;Moore et al, 1994;Mottram et al, 2002;Murphy et al, 2007;Musser et al, 2001;Robinson & Sheridan, 2000;Schanding & Sterling-Tumer, 2010). Thus, it was hypothesized that the Mystery Motivator intervention would lead to a decrease in dismptive classroom behavior.…”
Section: Purpose Of the Studymentioning
confidence: 70%
“…The majority of studies conducted on the efficacy of the Mystery Motivator have employed an individual independent contingency or an independent group contingency to facilitate behavioral and academic change (DeMartini-ScuUy, Bray, & Kehle, 2000;Kehle, Madaus, Baratta, & Bray, 1998;LeBlanc, 1998;Madaus, Kehle, Madaus, & Bray, 2003;Matovic, 2010;Moore, Waguespack, Wickstrom, Witt, & Gaydos, 1994;Mottram, Bray, Kehle, Broudy, & Jenson, 2002;Musser, Bray, Kehle, & Jenson, 2001;Robinson & Sheridan, 2000). Because reinforcement is delivered individually in such contexts, these interventions can be time intensive, inefficient, and complicated to implement.…”
Section: Mystery Motivatormentioning
confidence: 99%
“…Mystery rewards/reinforcers were used less often in special education classrooms as compared to general education classrooms. However, the studies using mystery rewards/reinforcers in special education classrooms (Groves & Austin, 2017;Musser et al, 2001) had large effect sizes similar to the ones in general education classrooms (Mottram et al, 2002;Robichaux & Gresham, 2014). The finding indicated that special education classrooms may benefit from using mystery rewards/reinforcers and should consider employing mystery rewards/reinforcers more frequently.…”
Section: Implication For Future Practicementioning
confidence: 87%
“…Previous studies have demonstrated efficacy of the MM intervention with a variety of participants. Specifically, MM is effective in increasing supporting outcomes in early childhood (Pre-K; Ling & Barnett, 2013), elementary (Kraemer et al, 2012; Mottram et al, 2002), and secondary (Theodore et al, 2001) educational settings. In addition, a dichotomous version of participant gender will be evaluated, consistent with reporting in previous studies.…”
Section: The MM Interventionmentioning
confidence: 99%